Genomic Characterization and Probiotic Potency of Bacillus sp. DU-106, a Highly Effective Producer of L-Lactic Acid Isolated From Fermented Yogurt - Li, Pan; Tian, Wenni; Jiang, Zhuo; Liang, Zuanhao; Wu, Xueyin; Du, Bing (Frontiers in Microbiology, 2018)
Bacillus sp. DU-106, a newly isolated member of Bacillus cereus group, exhibits the predominant ability to produce L-lactic acid. The probiotic potency of test strain revealed its survivability at acidic pH, bile salts and viability in simulated gastric juice in vitro. The acute oral toxicity test indicated its no toxicity to laboratory mice in vivo. We further determined the complete genome of strain DU-106 to understand genetic basis as a potential probiotic. It has a circular chromosome and three plasmids for a total genome 5,758,208 bp in size with a G+C content of 35.10%. Genes associated with lactate synthesis were found in the DU-106 genome. We also annotated various stress-related, bile salt resistance, and adhesion-related domains in this strain, which likely provide support in exerting probiotic action by enabling adhesion to host epithelial cells and survival under gastrointestinal tract. Moreover, strain DU-106 genome lacks the virulence genes encodes cereulide synthetase, enterotoxin FM, and cytotoxin K. These phenotypic and genomic probiotic potencies facilitate its potential candidate as probiotic starter in food industry.